1995
DOI: 10.1111/j.1365-2621.1995.tb06292.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening Potato Starch for Novel Properties Using Differential Scanning Calorimetry

Abstract: THERMAL and other physicochemical properties of starch from 42 potato genotypes were studied to find those with unique properties for food use, and to analyze relationships between thermal and other physicochemical properties. Onset and peak transition temperatures and gelatinization enthalpy intercorrelated. Transition temperatures intercorrelated with pasting temperature using a Brabender Visco-amylograph. Gelatinization entbalpy correlated with Brabender pasting temperature and peak paste viscosity, and ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 27 publications
7
106
1
3
Order By: Relevance
“…Esses amidos poderiam substituir amidos quimicamente modificados ou abrir novos mercados para amidos [8].…”
Section: Discussionunclassified
“…Esses amidos poderiam substituir amidos quimicamente modificados ou abrir novos mercados para amidos [8].…”
Section: Discussionunclassified
“…Peak and final viscosities are important parameters, to have an understanding of product behaviour during and after processing. Liang and King (2003) reported on the pasting effects of lipids and amino acids on rice starch and various reports suggested that pasting characteristics (Lai 2001), rheological properties of paste and gels (Kim et al 1995;Wiesenborn et al 1994) and other functional properties (Zobel 1984) of flour and starches vary with species and variants.…”
Section: Introductionmentioning
confidence: 99%
“…Starch contributes greatly to the textural properties of many foods and has many industrial applications as a thickener, colloidal stabilizer, gelling agent and water retention agent. Interest in new value-added products such as chocolate, peanut butter, oleoresin, dextrines and adhesives to the industry has resulted in many studies being carried out on the morphological, rheological, thermal and textural properties of corn and potato starches (Evans and Haisman 1979;Kim et al 1995;Lii et al 1996). Native starch has limited industrial applications due to high tendency of retrogradation, shear resistance and thermal resistance; therefore there is the need for its modification.…”
Section: Introductionmentioning
confidence: 99%